2015
DOI: 10.1111/jcmm.12727
|View full text |Cite
|
Sign up to set email alerts
|

P2Y12 antagonist attenuates eosinophilic inflammation and airway hyperresponsiveness in a mouse model of asthma

Abstract: Leukotriene E4 (LTE4) that plays a key role in airway inflammation is expressed on platelets and eosinophils. We investigated whether blocking of the P2Y12 receptor can suppress eosinophilic inflammation in a mouse model of asthma because platelets and eosinophils share this receptor to be activated. BALB/c mice were sensitized by intraperitoneal injection of ovalbumin (OVA), followed by OVA nebulization. On each challenge day, clopidogrel, a P2Y12 antagonist was administered 30 min. before each challenge. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…We used considerably lower doses of Mon and Clo (10 mg/kg for each drug) compared to previous experimental studies. 18,26,27 The secondary, eosinophilic asthma mouse model manifested higher eosinophilic infiltration than the model that we used previously to clearly detect the therapeutic effects of Clo/Mon. The Clo/Mon treatment suppressed the lymphocyte count in BAL fluid, which explained the decreased levels of Th2 cytokines.…”
Section: Correlation Of Pea and Eosinophil Count With Inflammatory mentioning
confidence: 94%
See 2 more Smart Citations
“…We used considerably lower doses of Mon and Clo (10 mg/kg for each drug) compared to previous experimental studies. 18,26,27 The secondary, eosinophilic asthma mouse model manifested higher eosinophilic infiltration than the model that we used previously to clearly detect the therapeutic effects of Clo/Mon. The Clo/Mon treatment suppressed the lymphocyte count in BAL fluid, which explained the decreased levels of Th2 cytokines.…”
Section: Correlation Of Pea and Eosinophil Count With Inflammatory mentioning
confidence: 94%
“…16 Platelets and eosinophils share similar surface receptors, including the cysteinyl LT receptor type 1 (CysLTR1) and the P2Y12 purinergic receptor (P2Y12R). 18 Furthermore, LTE 4 , a P2Y12R and CysLTR1 agonist, induces eosinophilic inflammation following a platelet-dependent mechanism. 17 Our recent study suggested an inhibitory effect of clopidogrel (Clo), an antiplatelet drug that targets the P2Y12R, during eosinophilic inflammation and degranulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a clinical study involving cardiologic patients, Diehl et al showed that P2Y 12 mRNA was expressed in leukocytes obtained from leukapheresis and that P2Y 12 inhibition by clopidogrel decreased leukocyte CD11b (Mac-1) expression [59]. The P2Y 12 expression was also reported in human eosinophils in which P2Y 12 activation induced the release of eosinophil peroxidase [21] that could be prevented by clopidogrel [60]. Activation of P2Y 12 in macrophages induced cell spreading with formation of lamellipodia, and P2Y 12 inhibition alleviated chemotaxis [25].…”
Section: Role Of Non-platelet P2y 12 Receptorsmentioning
confidence: 98%
“…Furthermore, blocking P2Y 12 pathways alters T cell activation and changes the cell population (Vemulapalli et al, 2019). In the respiratory system, P2Y 12 receptor appears to contribute to inflammatory response, participating in allergic and non-allergic processes (Paruchuri et al, 2009;Shirasaki et al, 2013;Suh et al, 2016), as well as autoimmune disease processes (Domercq et al, 2018). Therefore, to better understand the role of purinergic signaling in silica-induced lung inflammation, we investigated the participation of P2Y 12 receptor in the onset of silicosis.…”
Section: Introductionmentioning
confidence: 99%